A Scottish family with Bazex-Dupré-Christol syndrome: follicular atrophoderma, congenital hypotrichosis, and basal cell carcinoma. Issue 6 (June 1996) - Kidd, A; Carson, L; Gregory, D W; de Silva, D; Holmes, J; Dean, J C; Haites, N
Abstract : Bazex-Dupre-Christol syndrome (BDCS) is an X linked dominant disorder of the hair follicle characterised by follicular atrophoderma, multiple basal cell carcinomas, hypotrichosis, milia, and localised hypohidrosis. Follicular atrophoderma (FA) are follicular funnel shaped depressions, "ice pick marks", seen most commonly on the dorsum of the hands. We describe the first known Scottish family with this syndrome, five affected members spanning three generations. They have hypohidrosis confined to the face, coarse hair, dry skin, milia, and follicular atrophoderma. All the adults have a history of multiple basal cell carcinomas. None of them has any skeletal feature suggestive of Gorlin's syndrome. The clinical features, skin histology, and scanning electron microscopic (SEM) examination of the hair are described and illustrated. The features are compared with 15 previous reports of BDCS and four reports in which this is a possible diagnosis are also reviewed. BDCS should be considered as a differential diagnosis in patients with early onset or familial basal cell carcinomas.